Usability Evaluation of IIUM Online Digital Manuscript Interface - Mansor, Yushiana; Mat Ripin, Faizal Hazri (University of Nebraska--Lincoln Libraries, 2013)
Manuscripts are among the special collections of most libraries. The collection of manuscripts of the International Islamic University Malaysia (IIUM) library can be retrieved from the Digital Manuscript interface of the IIUM Library website. User evaluation of the interface is much needed to enable library administration know users’ experience while interacting with the interface. This study attempts to evaluate the effectiveness, efficiency and user satisfaction with the IIUM Digital Manuscript interface among the library users, based on the usability metrics established by the American National Standards Institute (ANSI). Questionnaires were administered to gather information about users’ background and their satisfaction with the use of the interface. In addition, each respondent was given eight tasks that have been specifically designed to measure their ability to navigate within the digital manuscript interface of the library. Findings indicate that despite some of the shortcomings observed with the interface design, respondents were able to complete the tasks assigned, though at different completion duration. They were also satisfied with the overall design of the interface. Comments and recommendations given by the respondents were as well reported.